Suspended and immobilized biomass in individual wastewater treatment systems SBR and SBBR. Issue 50 (26th October 2016) - Sowinska, Aleksandra; Makowska, Małgorzata
Abstract: The small wastewater treatment plant is a device or group of devices which—through mechanical, biological, and chemical processes—reduces the pollution load to the values specified in the Regulation of the Minister of the Environment. The aim of this research is to show the relationship between the growth of the biomass and the effectiveness of removing contaminants from wastewater in individual wastewater treatment systems. The results of activated sludge volume after 30 min settling, microscopic analysis, and quantitative and qualitative parameters of biomass in the aeration chambers were analyzed in this article. During the research, one of the reactors was converted into a hybrid reactor (SBR filled with plastic carriers, which support the process of nitrification). A microscopic analysis of the biomass was conducted to evaluate the operation of activated sludge and biofilm. Flocs of activated sludge in the SBR were characterized by irregular shape and high biodiversity. The appearance of rotifers testified about the good condition of the sludge. The microscopic analysis of biomass of the hybrid reactor showed a negative effect of the applied biopreparation. Microorganisms such as bacteria and ciliates were observed in the biomass. In summary, the structure of the biofilm and activated sludge floc is very sensitive to the system parameters and external factors. Biofilm develops more slowly than the activated sludge. Introduction of the moving bed into the reactor of activated sludge should be made in the summertime.